PENGARUH LITERASI KEUANGAN DAN FINANCIAL SELF-EFFICACY TERHADAP FINANCIAL MANAGEMENT BEHAVIOR MAHASISWA JURUSAN ADMINISTRASI BISNIS - Nisrina Ayu Lestari; Mohammad Adhiya Riswandha (Business Administration, FISIP ULM, 2026)
The rapid development of digital financial technology, particularly e-wallets, has significantly changed students’ financial behavior patterns. However, the convenience of digital transactions is not always matched by adequate financial management skills. This study aims to examine the influence of financial literacy and Financial Self-Efficacy on the Financial Management Behavior of students who use e-wallets. Using a quantitative method and involving 218 respondents, the data were analyzed using multiple linear regression. The results show that Financial Literacy and Financial Self-Efficacy have a positive and significant effect on Financial Management Behavior, both partially and simultaneously, with a combined contribution of 59.6%. This study concludes that sound financial behavior stems from a combination of financial knowledge and self-efficacy. In practical terms, these findings encourage educational institutions to integrate digital-based financial education into their curricula to foster a generation that is more financially literate.